The princess and the kiss : [a story of God's gift of purity] - Bishop, Jennie; McDaniel, Preston (Anderson, IN : Warner Press, 1999)
"A loving king and queen present their daughter with a gift from God--her first kiss--to keep or give away. The wise girl waits for the man who is worthy of her precious gift ..."
Subtitle from cover.
Keywords: Princesses -- Fiction; Purity (Ethics) -- Fiction; Princesses -- Fiction; Purity (Ethics) -- Fiction; Princesses; Purity (Ethics); Fiction